2011
DOI: 10.1016/j.molcel.2011.08.032
|View full text |Cite
|
Sign up to set email alerts
|

In Embryonic Stem Cells, ZFP57/KAP1 Recognize a Methylated Hexanucleotide to Affect Chromatin and DNA Methylation of Imprinting Control Regions

Abstract: SummaryThe maintenance of H3K9 and DNA methylation at imprinting control regions (ICRs) during early embryogenesis is key to the regulation of imprinted genes. Here, we reveal that ZFP57, its cofactor KAP1, and associated effectors bind selectively to the H3K9me3-bearing, DNA-methylated allele of ICRs in ES cells. KAP1 deletion induces a loss of heterochromatin marks at ICRs, whereas deleting ZFP57 or DNMTs leads to ICR DNA demethylation. Accordingly, we find that ZFP57 and KAP1 associated with DNMTs and hemim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
600
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 522 publications
(652 citation statements)
references
References 43 publications
32
600
4
1
Order By: Relevance
“…Imprinting of IGF2 is 15 regulated at the IGF2-H19 ICR, and ZFP57 binds to this region in ES cells. 27 In this study, we also observed the binding of ZFP57 to the IGF2-H19 ICR in HT1080 cells.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Imprinting of IGF2 is 15 regulated at the IGF2-H19 ICR, and ZFP57 binds to this region in ES cells. 27 In this study, we also observed the binding of ZFP57 to the IGF2-H19 ICR in HT1080 cells.…”
Section: Discussionsupporting
confidence: 60%
“…26 Several reports have suggested that this transcription factor binds to KRAB-associated protein 1 (KAP1), a scaffold protein for various heterochromatin-inducing factors, through its KRAB domain, and is involved in genome imprinting by recruiting KAP1 to several ICRs. 26,27,33 In addition, mutations in the ZFP57 gene result in transient neonatal diabetes mellitus type 1, possibly through Plagl1 overexpression. 34,35 The role of ZFP57 in tumorigenesis has not been elucidated yet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations in genes encoding members of the zinc-finger protein family have been considered good candidates as causative defects of MLID, given the well-established role of ZFP57 mutation in patients with transient neonatal diabetes mellitus and MLID [26,27]. However, no mutations have been found to date in other members of the protein family in MLID patients.…”
Section: Introductionmentioning
confidence: 99%